Relevansi Aliran Naturalisme terhadap Permasalahan Lingkungan Berbasis Pendekatan Deep Learning - Amelia Putri; Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Modern education faces challenges in realizing meaningful learning that is grounded in students’ real-life experiences. One effort to address this challenge is through the integration of the philosophy of naturalism with the deep learning approach. This study aims to analyze the relevance of the philosophy of naturalism and the deep learning approach in biology learning, particularly on the topic of environmental waste issues. The method used is a literature study (library research) by examining various scientific sources such as journals, books, and previous research related to both topics. The findings indicate that the philosophy of naturalism emphasizes the importance of a learning process that is in harmony with nature and based on students’ empirical experiences. Meanwhile, the deep learning approach promotes meaningful, mindful, and joyful learning, enabling students to understand concepts deeply and contextually. The integration of both can enhance the effectiveness of biology learning, especially in fostering awareness and responsibility towards the environment. In conclusion, the synergy between the philosophy of naturalism and the deep learning approach serves as a relevant and practical strategy for improving the quality of biology education while shaping students’ character to be environmentally conscious, particularly regarding waste management